Challenges of the Output- Employment Growth Imbalance in Transition Economies - Mihajlović, Vladimir; Marjanović, Gordana (Naše gospodarstvo/Our economy, 2021)
The trade-off between output and unemployment has become an essential part of modern macroeconomics and is known as Okun's law. However, in transition and emerging markets economies' context, the output-employment nexus has a much more important role as these countries strive to significantly improve the growth dynamics of both variables. This paper aims to analyze the particularities of this relationship in selected Central- and South-Eastern European transition (and former transition) countries to find out a discrepancy between the output and employment growth. Therefore, the employment elasticity coefficients are calculated. The estimated results suggest that, in the observed period, economic growth has not contributed to satisfactory employment growth, which is commonly referred to as a "jobless growth" hypothesis. Accordingly, this paper attempts to single out the main challenges of the output-employment growth misbalance in these countries and propose adequate policy measures that could reduce it. The industrial policy that differentiates from the "one-size-fits-all" paradigm is emphasized as the most important part of macroeconomic policy in transition economies to make their development more balanced. Additionally, short-run stabilization policy, especially the one focused on the labour market, has a significant role in these economies.
Keywords: economic growth; employment elasticity; Okun’s law; labour market; transition economies